Development of a Risk Based Underwater Inspection (RBUI) Methodology for Malaysia Fixed Offshore Structure - Sambu Potty, Narayanan (2011)
Malaysia has several hundred platforms located domestically that require underwater inspections on a regular basis. Because of the high cost of underwater inspections, a fully developed risk-based process should be implemented to more effectively plan inspection resources. The process identifies which platforms exposed to the greatest risk and which platforms are most likely to benefit the most from a more focused inspection effort. The platforms are then ranked from highest to lowest risk, with the highest risk platforms receiving priority for inspections. The use of RBUI for inspection planning is demonstrated in the paper.